Contaminación y pérdida de biodiversidad por actividades mineras y agropecuarias: estado del arte - Paredes-Vilca, Oscar Junior (2024)
The services provided by biodiversity and ecosystems are endangered by the various activities carried out by man. Among them, mining and agricultural activities have contributed to the loss of biodiversity and deterioration of ecosystems, but the damage caused by mining is overshadowed by the economic benefits it brings. Thus, the objective of this study was to compile scientific literature that helps determine the way in which these activities harm biodiversity and ecosystems, as well as the negative effects they trigger between them. To do so, original and review articles from the Web of Science, Scopus and Scielo databases were used. The findings show that there is contamination with heavy metals, a product of mining and the use of agrochemicals by agricultural activity. However, there are negative externalities generated in a unidirectional way, with agricultural production subject to the damage caused by mining.